WRITERS-ENLIGHTENERS AND EUROPEAN OF UKRAINIAN-FOREIGN LITERARY MUTUAL RELATIONS - Matviishin, V. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the question is ponderable payment of the Ukrainian writers of ХІХ age in the matter of expansion of literary communications between the East and the West by a selection and recreation by Ukrainian of the best standards of the west European writing.